Schizandrol A reverses multidrug resistance in resistant chronic myeloid leukemia cells K562/A02 - Arken, Nurguli (Cellular and Molecular Biology, 2019)
Overexpression of P-gp is the main cause of multidrug resistance (MDR) and chemotherapeutic failure in leukemia. In this study, the multidrug resistance reverse effect of Schizandrol A (SchA) was demonstrated with P-gp overexpressed drug-resistant K562/A02 cells. SchA had almost no cytotoxic activity, the EC50 value reversed to DOX was in the nanomole range of (707 ± 29nM) and had a high selectivity index (> 113) to normal cells. DOX accumulation and Rh123 efflux tests demonstrated that the MDR reversal activity of SchA was induced by inhibiting P-gp function. Western blotting assay showed that SchA down-regulated the expression of P-gp by inhibiting the PI3K / Akt signaling pathway, which was also a key factor in reversal activity. Therefore, SchA may be a potential candidate for natural MDR reversal agents.